2019
DOI: 10.3389/fphys.2018.01935
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Associations of Blood-Based Nutrient Profiling With Body Composition in the Elderly

Abstract: The intake of adequate amounts and types of nutrients is key for sustaining health and a good quality of life, particularly in the elderly population. There is considerable evidence suggesting that physiological changes related to age and sex modify nutritional needs, and this may be related to age-associated changes in body composition (BC), specifically in lean and fat body mass. However, there is a clear lack of understanding about the association of nutrients in blood and BC parameters in the elderly. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Likewise, the Cu/Zn ratio did not indicate sex-specific differences, but total copper levels in the serum of female patients were more strongly elevated than those in male patients. The latter was also observed in healthy adult women, who have significantly higher serum copper concentrations than those of men, which was also reflected by a higher serum Cu/Zn ratio [ 51 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Likewise, the Cu/Zn ratio did not indicate sex-specific differences, but total copper levels in the serum of female patients were more strongly elevated than those in male patients. The latter was also observed in healthy adult women, who have significantly higher serum copper concentrations than those of men, which was also reflected by a higher serum Cu/Zn ratio [ 51 ].…”
Section: Discussionmentioning
confidence: 92%
“…Sex-dependent characteristics in trace-element homeostasis affecting serum levels are mainly known for selenium and copper [ 51 , 52 ]. So far, sex-specific differences in free serum zinc levels were observed in humans and mice [ 27 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive clinical and molecular characterization was performed at baseline and after the 1-year intervention, and results achieved so far in the framework of this study have demonstrated a beneficial effect of the Mediterranean-like diet on global cognition and episodic memory (Marseglia et al 2018), osteoporosis , immune function (Maijo et al 2018), and cardiovascular health , as well as on the proteasomal proteolysis (Athanasopoulou et al 2018). The NU-AGE study design (different countries with different dietary traditions and habits) and the large number of collected data allowed to evaluate the impact of relevant variables usually poorly investigated (age, sex, and ethnicity/genetics, as well as individual characteristics) on different parameters at baseline and after the intervention (Konz et al 2018;Marseglia et al 2018;Ostan et al 2018;Pujos-Guillot et al 2018;Santoro et al 2018Santoro et al , 2019Jennings et al 2019). Importantly, the enrolled subjects were recruited also in non-Mediterranean countries (Poland, the Netherlands, and the UK).…”
Section: Introductionmentioning
confidence: 99%
“…Ethanolamine is known to stimulate the generation of phosphatidylethanolamines, membrane phospholipids that have a wide range of structural and functional properties, including lipid synthesis, mitochondrial biogenesis, and autophagy (43). Less is known about plasma ethanolamine, although it is suggested to be a positive marker of skeletal muscle turnover (44). Our study found no correlation between the weight of the gastrocnemius and ethanolamine level, and even a negative correlation between limb grip strength and plasma ethanolamine level, indicating more research is needed to confirm its impact, or lack thereof, on muscle tissue.…”
Section: Discussionmentioning
confidence: 99%